Evaluation of antifungal and phytochemical activity from different parts of cerbera odollam gaertn - Chu, Sue Yin (School of Bioprocess Engineering, 2016)
Aspergillus niger, Fusarium oxysporum and Penicilium citrum are common post-harvest pathogens. The scope of the study is to investigate the anti-fungal activity from different parts of crude extracts of Cerbera odollam e.g leaf, flower, fruit, seeds, wood and bark against these pathogens. Group of bio-compounds were determined by standard phytochemical test and the antifungal bioassay were carried out on laboratory scale